BUDAYA INDONESIA DALAM VIDEO KLIP COLDPLAY “AMAZING DAY” (ANALISIS SEMIOTIKA ROLAND BARTHES) - Antonio C. A. Amaral (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Abstract:In communication science the role of art is the content of messages in form of visual, audio, audiovisual. The purpose of this study was to find out Indonesian culture in the Coldplay "Amazing Day" video clip. The method used in this study is a qualitative method and uses Roland Barthes semiotics analysis method. Scene I of Saman Dance from Aceh the cultural value that can be taken is the association without borders / separator dividing in the community. Scene II Mask Dance from this Mask can also be interpreted as a veil. Scene III Bali Culture Balinese culture cannot be separated from religion / religion. The conclusions drawn from the five scenes in the video clip "Amazing Day" are the meaning of the denotation of the three Indonesian cultures contained in the video clip giving an overviewus not to forget the culture. The meaning of connotation the message that the way to give thanks is not only through prayer. Myths the way to dress in every culture shows the characteristics of certain regions. Keywords: Culture, Video Clips, Roland Barthes Semiotisc. Abstrak: Dalam ilmu komunikasi peranan seni sebagai isi pesan dalam bentuk visual, audio, audiovisual. Tujuan dari penelitian ini adalah untuk mengetahui budaya Indonesia dalam video klip Coldplay “Amazing Day”. Metode yang digunakan dalam penelitian ini yaitu metode kualitatif dan menggunakan metode analisis semiotika Roland Barthes. Adegan I Tari Saman dari Aceh nilai budaya yang dapat diambil yaitu pergaulan tanpa batas/sekat pemisah dilapisan masyarakat. Adegan II Tari Topeng dari Topeng ini juga dapat dimaknai sebagai tabir. Adegan III Budaya Bali Budaya bali tidak terlepas dari religi/keagamaan.Kesimpulan yang diambil dari lima scene dalam video klip” Amazing Day” adalah Makna denotasi memberikan gambaran kepada kita agar tidak lupa budaya. Makna Konotasi Pesan bahwa cara mengucap syukur kepada Tuhan tidak saja melalui doa. Mitos Cara berbusana dalam setiap adegang budaya menunjukan ciri khas daerah tertentu. Kata Kunci: Budaya, Video Klip, Semiotika Roland Barthes.